Membaca Takdir : pemikiran dan jejak STA. - Dian Rakyat (Firm) (Jakarta : Dian Rakyat, 2010)
Critical analysis and interpretation on Sutan Takdir Alisyahbana's thoughts, an Indonesian novelist and author.
Includes bibliographical references.
In Indonesian, with two articles in English.
Keywords: Alisjahbana, S. Takdir -- 1908-1994 -- Criticism and interpretation; Novelists, Indonesian; Authors, Indonesian